Social and behavioral characteristics of male blood donors and their sexual partners: an analysis to define risk subsets. Issue 8 (3rd June 2019) - Salomon, Tassila; Gomes, Isabel; Ozahata, Mina Cintho; Moreira, Carlos Henrique Valente; Oliveira, Claudia Di Lorenzo; Gonçalez, Thelma T.; Duarte, Maria Esther; Miranda, Carolina; Carneiro Proietti, Anna Bárbara; Sabino, Ester; de Almeida Neto, Cesar; Custer, Brian; et al.
Abstract : BACKGROUND: Men who have sex with men in Brazil are deferred from donation for 1 year since their last sexual contact. Legal proceedings in front of the Brazilian Supreme Court could compel blood collection agencies to discontinue use of sexual orientation questions. METHODS: Data from male participants in a completed HIV risk factor case‐control study were used to evaluate whether it is possible to differentiate donors at lower and higher risk for HIV using two analytical approaches: latent class and random forest analyses. RESULTS: Male blood donors were divided into three distinct risk profile classes. Class 1 includes donors who are heterosexual (96.4%), are HIV negative (88.7%), have a main partner (99.4%), and practice unprotected sex (77.8%). Class 2 includes donors who are men who have sex with men /bisexuals' (100.0%), are HIV positive (97.4%), and were not aware of their sexual partners' HIV status (80.3%). Class 3 includes donors who are heterosexual (84.1%), practice unprotected vaginal/anal heterosexual sex (66.8% vs. 40.9%), and were both HIV positive and HIV negative (49.5% vs. 50.5%). We also found that asking donors about their partner(s)' HIV serostatus could replace asking about donors' sexual orientation and types of partners with relatively minor shifts in sensitivity (0.76 vs. 0.58), specificity (0.89 vs. 0.94), and positive predictive value (0.85 vs. 0.88). CONCLUSION: Sexual orientation questions on the donor questionnaire could be replaced without great loss in the sensitivity, specificity, and positive predictive value. Social and sexual behaviors of donors and their partners are proxies for HIV risk and can help to develop modified questions that will need controlled trials to be validated.